You are not logged in.
Pages: 1
never mind,
it doesnt have odd symmetry
This setup
2A = (1+e^B)e^C + (1+e^(-B))e^(-C)
is similar to drift-diffusion in a transistor .
We couldn't get it into closed form unless we made some assumptions.
is there anything special about
C1, MD/H and MR/H
like MR/H+C1 ≈ C1
this would be nice
Anyone know how to do regression analysis of a shifted exponential curve.
here is the data
1 0.997706596
2 0.243081214
3 0.079426264
4 0.03319443
5 0.016202707
6 0.00969521
7 0.007108719
8 0.004852038
9 0.003415406
10 0.002462571
11 0.001977777
the equation should look like a^((-x+1)/b) i think.
I cant seem to do it with my calculator it doesn't handle the shift.
Thanks
f(x)= [(x^3) - 3(x^2) + 4]/x^2
divide through by x^2
you get
f(x) = x - 3 + 4x^(-2)
use the power rule f(x) = x^n f'(x) = n*x(n-1)
f'(x) = 1 - 8*x^(-3)
then factor out x^(-3)
[x^3 - 8]*x^(-3) = [(x^3)-8]/x^3
cosh(x) can be approximated with a taylor expansion.
its the same as the expansion for cosine
1 + x²/2 + x^4/ 24+ ....
1/4(2+Cos[2(a-b)]+Cos[2(a+b)]-2Cos[c]Sin[a]Sin) <- something seems wrong here
Sin needs a variable.
if a = 0 b= pi/4
you get 1/2
but you might be able to get something smaller than that.
You might try taking partial derivatives of Cos[2(a-b)]+Cos[2(a+b)] wrt a & b and look for extrema. You could also try to write an excel spread sheet which tries different combinations of a & b and use the goal seek function.
I am in a hurry but I will try to work on it later.
About myself...
25/m/Ca
EE student at UC Davis
hobbies: cycling, skating, surfing although there are no oceans near davis
A . (A + 3B +7C) = A.A + 3(A.B) + 7(A.C)
A.B and A.C are given
A . (A + 3B +7C) = A.A +(3*3) +(7*-1)
A . (A + 3B +7C) = A.A + 2
whats A.A
X.Y = |X|*|Y| * cos(θ)
A is PARALLEL to A there for θ = 0
or
The angle between A and A is 0
cos(0) = 1
A.A = 4
A . (A + 3B +7C) = 4 + 2 =6
hope that helps
edit: previously i said normal
∫ ( ln(x)/x ) dx or ∫ (dx/x) *ln(x)
let u= ln(x)
du/dx = 1/x or du = dx/x
replace dx/x with du
and ln(x) with u
then you are left with ∫ u du == u²/2
thats where the 2 comes from.
Pages: 1